2020
DOI: 10.1002/net.21967
|View full text |Cite
|
Sign up to set email alerts
|

Integrating production scheduling and transportation procurement through combinatorial auctions

Abstract: This study uses the winner determination problem (WDP) to integrate auction transportation procurement with decisions related to production scheduling. The basic problem arises when a manufacturer has to clear a combinatorial auction to decide whether to cover transportation needs by using the in‐house fleet or to procure transportation through auction. Thus, the manufacturer should include an additional decision level by integrating the WDP with production scheduling to gain efficiency and achieve savings in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Moreover, the authors proposed three metaheuristic approaches for its solution. The last work we are aware of was developed by Triki et al (2020) in which the SLSP model has been embedded within a production-distribution framework while involving occasional drivers that contribute in accomplishing part of the delivery tasks. Their study has shown that the SLSP can gain efficiency, expressed in terms of total cost minimization, by coordinating the production and delivery activities.…”
Section: Pre-auction Phase: Isp Modelsmentioning
confidence: 99%
“…Moreover, the authors proposed three metaheuristic approaches for its solution. The last work we are aware of was developed by Triki et al (2020) in which the SLSP model has been embedded within a production-distribution framework while involving occasional drivers that contribute in accomplishing part of the delivery tasks. Their study has shown that the SLSP can gain efficiency, expressed in terms of total cost minimization, by coordinating the production and delivery activities.…”
Section: Pre-auction Phase: Isp Modelsmentioning
confidence: 99%
“…Transportation is considered one of the important elements that have a fundamental role in designing the supply chain [28]. There are critical impacts associated with transportation such as global warming, environmental deterioration, health effects (physical, emotional, mental, spiritual), and greenhouse gas emissions [23].…”
Section: Transportationmentioning
confidence: 99%
“…Multi‐objective optimization models were presented by Ignatius et al [19] who considered the cost, market fairness, and market confidence as criteria for choosing the winning bids. Ledyard et al [27] and Elmaghraby and Keskinocak [10] developed specialized models for real‐life applications and Triki et al [46] embedded a WDP within a production‐distribution planning scheme.…”
Section: Literature Reviewmentioning
confidence: 99%